2017
DOI: 10.14202/vetworld.2017.331-335
|View full text |Cite
|
Sign up to set email alerts
|

Hemato-biochemical alterations and urinalysis in dogs suffering from benign prostatic hyperplasia

Abstract: Aim:The study was designed to evaluate the hemato-biochemical alterations, urinalysis along with histomorphological and histological changes of prostate glands in dogs affected with benign prostatic hyperplasia (BPH) in and around Bhubaneswar, Odisha, India.Materials and Methods:In toto, 445 dogs presented to the Teaching Veterinary Clinical Complex of the College of Veterinary Sciences and Animal Husbandry, one Government Veterinary Hospital and two pet clinics in and around Bhubaneswar screened for the prese… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 10 publications
2
7
0
Order By: Relevance
“…Te same trend happened to the WBCs, and their percentages didn't change signifcantly (Table 4), which was similarly in line with the previous studies [1,36].…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…Te same trend happened to the WBCs, and their percentages didn't change signifcantly (Table 4), which was similarly in line with the previous studies [1,36].…”
Section: Discussionsupporting
confidence: 91%
“…Regarding the hematological parameters, it was observed that the EELR in both doses didn't cause a signifcant change between the dogs with BPH and the healthy dogs, as it had in the previous studies [1,36]. Tis issue demonstrated that there was no blood toxicity following the consumption of the EELR.…”
Section: Discussionsupporting
confidence: 57%
See 1 more Smart Citation
“…BPH is the most common prostatic disease diagnosed in the dog and affects approximately 80% of intact male dogs over 5 years old (Sirinarumitr et al, ) and more than 95% of intact male dogs over 9 years old (Gobello & Corrada, ). Large breeds such as Doberman, German Shepherd, Rhodesian Ridgeback and Labrador Retriever appear to be predisposed to BPH (Das, Patra, Das, Rath, & Mishra, ; Polisca, Troisi, Fontaine, Menchetti, & Fontbonne, ; Wolf et al, ). Several theories have been proposed to explain the aetiology, but only three facts have proven to be implied in both species: The incidence of BPH increases with advanced age; The presence of functioning testes is required; Dihydrotestosterone (DHT), the active metabolite of testosterone, is more concentrated in hyperplastic prostatic tissue compared to normal tissue. …”
Section: Benign Prostatic Hyperplasiamentioning
confidence: 99%
“…Sometimes the organ is not symmetric because of large intraparenchymal cysts or the cobblestone‐like appearance of its surface (Lopate, ). Haematologic findings and urinalysis are usually normal even if haematuria may be present (Das et al, ) and the prostatic fraction of seminal plasma too is frequently haemorrhagic. Aerobic and anaerobic cultures of seminal plasma and urine are negative (Read & Bryden, ), while cytology and bacterial culture of prostate secretions may be useful to exclude or to confirm the concomitance of multiple prostatic disorders, even if do not provide definitive diagnosis of BPH (Greer, ).…”
Section: Benign Prostatic Hyperplasiamentioning
confidence: 99%